Effect of a maximal strength mesocycle on muscle strength, muscle power, and jump ability in a Superleague volleyball team - Gómez-Puerto, J. R.; da Silva-Grigoletto, M. E.; Viana-Montaner, B. H.; Beas-Jiménez, J. D.; Centeno-Prada, R.; Melero-Romero, C.; Vaamonde, D.; Garcia-Manso, J. M.; Ugrinowitsch, C. (Archivos de medicina del deporte, 2008)
Muscle strength development is a traditional objective in training among almost all sport modalities. More specifi cally, in volleyball, the inherent characteristics of this modality makes necessary for players to incorporate strength specifi c exercises to their training routines. Many volleyball coaches think that maximal strength training is detrimental for jump ability, and, therefore, such mesocycles are not normally included as part of their training routines near or within a competition period. However, literature presents data regarding an increase of jump ability due to strength training. Thus, the purpose of this study was to verify the effect of a maximal strength mesocycle on the following variables for lower body: muscle strength, muscle power, and jump ability. Secondarily, the effect of the abovementioned mesocycle on upper body was also assessed, analyzing muscle strength, and muscle power. Methods: Eleven professional volleyball players (Superleague) participated in this short-term study. Muscle performance was assessed though jump (CMJ), muscle strength (4RM), and muscle power tests both before and after a maximal strength mesocycle. Traditional exercises for lower body (half squat, calf raises) and superior body (bench press and pullover) strength development were used. Results: There were not signifi cant differences for CMJ values between pre-test and post-test (38,12 ± 2,63 vs. 38,25±2,78 cm; P > 0,05). On the other hand, muscle strength and power of the lower body experimented a statistically significant increase: 8.15% (103,15 ± 18,02 vs. 112,30 ± 17,80 kg; P < 0,05) and 2.22% (979,88 ± 89,62 vs. 1002,14 ± 109,31; P < 0,05), respectively. Likewise, statistically significant improvements have been observed for upper body: 10.63% (41,61 ± 5,75 vs. 46,56 ± 4,99; P < 0,05) for muscle strength, and 9.16% (200,88 ± 33,76 vs. 221,13 ± 43,76; P < 0,05), for muscle power. Conclusions: The use of a short-term maximal strength mesocycle during a season`s beginning might improve muscle strength and power without a detrimental effect in professional volleyball players.